Now that's what I call Motown [compact disc]. - Strong, Barrett; Reeves, Martha; Wells, Mary, 1943-1992; Gaye, Marvin; Terrell, Tammi; Wonder, Stevie; Robinson, Smokey, 1940-; Ross, Diana, 1944-; James, Rick, 1948-2004 (Universal Music, 2009)
The NOW series delves into the world of Motown. Includes 25 of the most beloved and timeless classic R & B tracks from some of the greatest musical artists of all time on one CD.